Liquid biopsy detection of genomic alterations in pediatric brain tumors from cell-free DNA in peripheral blood, CSF, and urine. Issue 8 (4th January 2022) - Pagès, Mélanie; Rotem, Denisse; Gydush, Gregory; Reed, Sarah; Rhoades, Justin; Ha, Gavin; Lo, Christopher; Fleharty, Mark; Duran, Madeleine; Jones, Robert; Becker, Sarah; Haller, Michaela; et al.
Abstract: Background: The ability to identify genetic alterations in cancers is essential for precision medicine; however, surgical approaches to obtain brain tumor tissue are invasive. Profiling circulating tumor DNA (ctDNA) in liquid biopsies has emerged as a promising approach to avoid invasive procedures. Here, we systematically evaluated the feasibility of profiling pediatric brain tumors using ctDNA obtained from plasma, cerebrospinal fluid (CSF), and urine. Methods: We prospectively collected 564 specimens (257 blood, 240 urine, and 67 CSF samples) from 258 patients across all histopathologies. We performed ultra-low-pass whole-genome sequencing (ULP-WGS) to assess copy number variations and estimate tumor fraction and developed a pediatric CNS tumor hybrid capture panel for deep sequencing of specific mutations and fusions. Results: ULP-WGS detected copy number alterations in 9/46 (20%) CSF, 3/230 (1.3%) plasma, and 0/153 urine samples. Sequencing detected alterations in 3/10 (30%) CSF, 2/74 (2.7%) plasma, and 0/2 urine samples. The only positive results were in high-grade tumors. However, most samples had insufficient somatic mutations (median 1, range 0-39) discoverable by the sequencing panel to provide sufficient power to detect tumor fractions of greater than 0.1%. Conclusions: Children with brain tumors harbor very low levels of ctDNA in blood, CSF, and urine, with CSF having the most DNA detectable. Molecular profiling is feasible in a small subset of high-grade tumors. The level of clonal aberrations per genome is low in most of the tumors, posing a challenge for detection using whole-genome or even targeted sequencing methods. Substantial challenges therefore remain to genetically characterize pediatric brain tumors from liquid biopsies.